Peningkatan Produktivitas Tanah Pasir untuk Pertumbuhan Tanaman Kedelai dengan Inokulasi Mikorhiza dan Rhizobium - Saptiningsih, Endang - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2007)
Mycorhiza and Rhizobium were potensial soil nutrient-enriched organisms. This research was purposed tostudy effect of Mycorrhiza and Rhizobium inoculation in increasing the productivity of sand soil for the growth ofsoybean crops. This research arranged with four treatments: without inoculation(Po), with rhizobium inoculation(Pr), with micorrhiza inoculation (Pm), with micorrhiza-rhizobium inoculation (Pmr). The data that was analysed byANAVA and DMRT at 5% level test. The result of study showed that the productivity of the sand soil could beincreased with mikorhiza and rhizobium inoculation indicated by increasing of soybean growth.